2010
DOI: 10.1186/1471-2474-11-116
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, characteristics, and impacts of work-related musculoskeletal disorders: a survey among physical therapists in the State of Kuwait

Abstract: BackgroundPhysical therapists working in the State of Kuwait are at risk of work-related musculoskeletal disorders (WMSDs). However, prevalence rates and risk factors are not well documented. The objective of this study was to determine the prevalence, characteristics, and impacts of WMSDs among physical therapists in the State of Kuwait.MethodsA self-administered questionnaire was distributed to 350 physical therapists. The questionnaire gathered demographic data as well as information on occurrence of muscul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
68
8
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 17 publications
9
68
8
9
Order By: Relevance
“…The low back is the body part with the highest WRMD prevalence, having been reported as 26% by Salik and Ozcan 1) , 28.8% by Molumphy et al 16) , 32.0% by Alrowayeh et al 19) , 35% by West and Gardner 11) , 45.0% by Bork et al 10) , 44% by Glover et al 12) , 51.7% by Nordin et al 21) , 56.5% by Grooten et al 20) , 62.5% by Cromie et al 9) , and 69.8% by Adegoke et al 15) Shehab et al 22) observed that lifetime WRMD prevalence rate was 70% among physical therapists with low back pain patients, because physical therapists handled their patients using inappropriate body mechanics and wrong techniques. Nordin et al 21) observed that physical therapists using manual treatments experienced more stress in the spine than in the hands because they applied manual treatments in the standing position over a long time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The low back is the body part with the highest WRMD prevalence, having been reported as 26% by Salik and Ozcan 1) , 28.8% by Molumphy et al 16) , 32.0% by Alrowayeh et al 19) , 35% by West and Gardner 11) , 45.0% by Bork et al 10) , 44% by Glover et al 12) , 51.7% by Nordin et al 21) , 56.5% by Grooten et al 20) , 62.5% by Cromie et al 9) , and 69.8% by Adegoke et al 15) Shehab et al 22) observed that lifetime WRMD prevalence rate was 70% among physical therapists with low back pain patients, because physical therapists handled their patients using inappropriate body mechanics and wrong techniques. Nordin et al 21) observed that physical therapists using manual treatments experienced more stress in the spine than in the hands because they applied manual treatments in the standing position over a long time.…”
Section: Discussionmentioning
confidence: 99%
“…5% in Cromie et al 9) , 69% in Molumphy et al 16) , 67% in Campo et al 14) , 73% in Glover et al 12) , 77.1% in Nordin et al 21) , and 80.0% in Bork et al 10) . Studies of WRMD prevalence in physical therapists in different countries indicate a prevalence of 47.6% in Kuwait 19) , 53.5% in Sweden 20) , 57.5-61% in the United States 10,14) , 67.5% in the United Kingdom 12) , 71.6% in Malaysia 21) , 85.0% in Turkey 1) , 54.8-91% in Australia 9,11) , and 91.3% in Nigeria 15) . The causes of WRMD included lack of personnel, bad working environments, and lack of equipment to reduce the burden on the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuwait developed work (17) found no correlation of musculoskeletal disorders with the gender of the therapist. In the present study, the number of respondents manual therapists females was higher than males, indicating that women are more susceptible to diseases of the DMEs.…”
Section: Discussionmentioning
confidence: 99%
“…In bivariate; Chi square analysis, the result of present study indicated that there were seven factors significantly associated with neck pain i.e. age, BMI, physical exercises, night shifts, neck bending, prolonged working hours on computer and personnel shortage.Further analysis, by using multiple logistic regression showed that age groups [30][31][32][33][34][35][36][37][38][39]) and [40][41][42][43][44][45][46][47][48][49] physical exercises (p= 0.025,, working time on computer (p= 0.029, night shifts (p= 0.001, personnel shortage (p= 0.005, and neck bending (p= 0.013, …”
mentioning
confidence: 99%